Die for love - Peters, Elizabeth (New York Harpercollins, 2011)
A librarian takes a trip to the convention of the Historical Romance Writers of the World, and when one of the attendees turns up dead and another is being threatened she becomes involved
1
Keywords: Librarians -- Fiction; Novelists -- Fiction